METHОDS FОR THE FОRMATIОN ОF MUSICAL LITERACY IN THE PERFОRMANCE ОF THE INSTRUMENT DUTОR (Scientific journal of the Fergana State University, 2024)
the article provides for methods for the formation of musical literacy in the performance of the dutor instrument, the work of the future dutor teacher on himself and self-assessment, improving his professional knowledge and using modern methods. The article focused on dutor, dutor prima instruments as all musical instruments have their place in Ham performance practice and their unique performance characteristics, one of the most basic features in students ' formation as mature performers is that they have a certain knowledge and sufficient skill in instrument performance techniques in practice, and develop the gamma, arpedjio, pitstsikato, which are necessary in mastering skilled performance techniques.